QR Code Based Attendance System as an Innovation for High School Management - Perwitasari, Ika Devi; Jodi Hendrawan; Nadya Andhika Putri; Yumna Tamimah Bilqis (Journal of Informatics Management and Information Technology, 2024)
This study aims to design and implement a QR Code-based attendance system as an innovation in managing student attendance at SMA Negeri 1 Binjai. Traditional paper-based or manual attendance systems often take a long time, are prone to errors, and are inefficient in archiving student attendance data. To overcome these obstacles, a QR Code-based attendance system was developed using scanning technology that allows each student to take attendance quickly and accurately. Using research and development methods, this system was designed through the stages of needs analysis, system design, development, and testing in the school environment. This system uses a mobile device combined with an online database, so that attendance data can be directly stored and accessed by the school in real-time. The test results showed that the QR Code-based attendance system was able to reduce attendance time from around 5 minutes to 1-2 minutes per class, increase the accuracy of attendance data recording, and automatically save data in the database. Surveys of users, namely students and teachers, showed a positive response, with 87% of students feeling that attendance was easier and more efficient, while teachers stated that this system reduced the administrative burden. This system also provides added value in terms of transparency, accuracy, and ease of access for teachers, students, and parents. This innovation is expected to be a solution in more modern and effective attendance management in other schools